Analysis of the genomic organisation and gene expression of brewery strains of yeast - Usher, Jane (Trinity College (Dublin, Ireland). Department of Microbiology, 2008)
The genomes of lager yeast arose from the fusion of two yeast strains most closely resembling Saccharomyces cerevisiae and Saccharomyces bayanus. The resultant strains have subsequently undergone genome duplications and rearrangements leading to the generation of a complex aneuploid genome. Genetic analysis has revealed that recombination between the two parent genomes has led to the presence of mosaic chromosomes.
Keywords: Microbiology, Ph.D.; Ph.D. Trinity College Dublin